NONADIABATIC RECTIFICATION CONTACT DEVICES - Voinov N.A.; Zemtsov D.A.; Zhukova O.P. (Техника и технология пищевых производств)
On the basis of the developed method of heat rectification implying partial condensation of the vapor mixture rising along the height of the column and the resulting evaporation of condensate before it is mixed with the main stream of the flowing reflux the process of strengthening the ethanol-water mixture in the contact levels with high and low mass exchange is investigated and intensified. The process of nonadiabatic rectification was carried out on the contact steps, and then held in the columns with 24 contact stages. The intensive mass transfer was achieved using a vortex steps performed by tangential swirlers. Contact stages of low-mass exchange were made of horizontally installed profiled copper plates. The paper presents the technological parameters which change the flow regime of the rotating layer on vortex stage. The value of the hydraulic resistance coefficient of the device is also determined. The dependence for determining the effectiveness of the contact stage was estimated by Murphree. The efficiency depends on the stage of the vortex flow ratio, fluid bed height, Reynolds centrifugal rotating layer, and the slope of the equilibrium curve. In the study of the steps made of the plates it was revealed that the greatest contribution to the strengthening of the mixture isallowed by the processes of evaporation and condensation occurring on the upper plate of the unit. The dependence was revealed for assessing the effectiveness of the contact stage of the plates, which depends on the specific expenditure reflux and steam mixture, condensation and evaporation surfaces, and steam radial velocity between the plates. To intensify the separation process the effected reflux rotation plates were disposed on the lower stage of each column by installing them on the motor shaft. It is shown that rotation of the liquid intensifies the mass transfer in the liquid and vapor phases. It is established, that the increasing number of revolutions of the plate and the concentration of volatile component in the mixture increases the efficiency of the stage that is caused by the intensification of stirring phases. While rotating the plates in the column reflux under heat rectification the overall efficiency of the stage increased 2 times. The highest efficiency of separation in distillation columns is achieved when the thermal difference between the steam temperature at the top stage and cooling water in this stage in a dephlegmator at is 8-25 °C. Recommendations for the use of the developed contact stages in columns thermal distillation are given.